ANALISIS PORTOFOLIO PRODUK PERUSAHAAN MELALUI PENDEKATAN BCG MATRIK DAN AKUNTANSI MANAJEMEN (STUDI KASUS PT. ANEKATAMA MAKMUR SENTOSA PANGKALPINANG) - Ferensia, Anastasia Angelina; Manullang, Rizal Ruben; Ahmad Agin, Arka'a (Jurnal Akuntansi Bisnis Dan Keuangan, 2020)
The research objective is to determine the company's product portfolio analysis through the BCG matrix approach and management accounting case study of PT Anekatama Makmur Sentosa Pangkalpinang. The method used in this research is qualitative method. Data analysis was performed using BCG matrices and break even points. Data analysis is through BCG matrix, which is through data collection of water pump product sales (1 inch / Radin, 2 inch / Spartan, and 3 inch / Loncin) company and water pump product sales data (1 inch / Word, 2 inch / Firman, and 3 inch / Firman) from competing companies. Data analysis through break even point is through collecting data from companies such as cost data per water pump product (1 inch / Radin, 2 inch / Spartan, and 3 inch / Loncin), revenue data per water pump product (1 inch / Radin , 2 inch / Spartan, and 3 inch / Loncin), and sales data per water pump product (1 inch / Radin, 2 inch / Spartan, and 3 inch / Loncin). Clarify costs, calculate contribution margins, and calculate break even points. Through the BCG matrix and break even point approach, it was found that the product 1 inch water pump (Radin) and 3 inch water pump (Loncin) were in the question mark position with break even point experiencing a profit of Rp 1.796.551 and Rp 3.184.470, the 2 inch water pump (Spartan) product is in the position of a lazy dog with a break even point experiencing a loss of (Rp. 3.726.330). So that the 1 inch water pump (Radin) and the 3 inch water pump (Loncin) can do a horizontal integration strategy to increase sales and market share, as well as Break Even Point. And a 2 inch water pump (Spartan) can do a product shrinkage strategy to reduce product costs in order to increase the profit of this product.